KEBEBASAN BERAGAMA YANG TERBATAS - Marsudi Utoyo (Faculty of Law, Universitas Diponegoro, 2013)
This article discusses religious freedom is restricted, the state gives the right to independence freedom to the their citizens for religious affairs. But the implementation in government gives freedom to the wiggle room restrictions of religious freedom. There are so many rules that restrict the rights and freedoms of minorities and is more concerned with the majority, resulting in religious conflicts.